Climate-displaced children and the protection of their education rights in Malaysia - Nurul Hidayat Ab Rahman,; Athirah Mohd Anuar,; Muhammad Zuhaili Mat Rani,; Mohamed Ruhizat Abdullah,; Azaraorni Abd Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The mobility crisis caused by climate change jeopardises the development rights of children, including their education. In 2019, approximately 23.9 million people were forcibly displaced by weather-related disasters, surpassing the 8.5 million people forcibly displaced by the most prevalent causes of migration and displacement, namely conflict and violence. Climate-displaced children in Malaysia face education barriers due to exclusion policies. Relocation brings procedural, financial, and linguistic hurdles, risking dropout. Thus, governments must examine the implications of climate change on the right to education and devise solutions to address this problem in order to achieve SDG 4 which aims to ensure inclusive and equitable quality education. This study will investigate the education rights of climate-displaced children under international and Malaysian law. In addition, the practises of Thailand and the United Kingdom will be observed, as these two countries with many climate-displaced children, have robust laws protecting their educational rights, warranting scrutiny. The work is based on doctrinal and comparative legal research, as related legal concepts, principles, and selected statutory materials are reviewed and compared to implement applicable practises in our country. The data were obtained via library research and analysed using content analysis. The preeminent factors are the child's best interests and the principle of equality. The results demonstrate that Malaysian legislation needs to adhere to international legal standards that recognise children relocated due to climate change as having a right to an education. To ensure every child's developmental potential, the government must adjust for inclusive, quality education.